2019
DOI: 10.3390/su11072050
|View full text |Cite
|
Sign up to set email alerts
|

Population Age Structure, Complex Socio-Demographic Systems and Resilience Potential: A Spatio-Temporal, Evenness-Based Approach

Abstract: The present study illustrates an original approach grounded on entropy theory and complex system thinking with the aim to investigate changes over time and space in population structure by age in Italy, in light of socioeconomic resilience and post-crisis recovery potential. Assuming that population structure may reflect different levels of resilience to exogenous shocks, a Pielou J evenness index was calculated on census data made available every 10 years (1861–2011) with the aim to identify compositional hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…Research by Vogelsang & Raymo (2014) showed that differences in the compisition of population play an important role in forming the observed relationships between the age structure at the local level and individual health. Cecchini et al (2019) note that the size of the population and its structure affect the regional resilience and are an important driving force of land use, while demographic trends make it possible to identify socioeconomic resilience and to formulate strategies aimed at encouraging faster recovery of local systems from external shocks. As noted by Kohler et al (2017), depopulation and aging have consequences beyond the scope of demography, since the aging will require better health and social care, which will increase costs, and tax revenues will decrease, just like local capacities for innovation and development, and depopulation will lead to a decline in effective delivery of services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Vogelsang & Raymo (2014) showed that differences in the compisition of population play an important role in forming the observed relationships between the age structure at the local level and individual health. Cecchini et al (2019) note that the size of the population and its structure affect the regional resilience and are an important driving force of land use, while demographic trends make it possible to identify socioeconomic resilience and to formulate strategies aimed at encouraging faster recovery of local systems from external shocks. As noted by Kohler et al (2017), depopulation and aging have consequences beyond the scope of demography, since the aging will require better health and social care, which will increase costs, and tax revenues will decrease, just like local capacities for innovation and development, and depopulation will lead to a decline in effective delivery of services.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of quality of life was reflected in the works of domestic and foreign scholars, because it is the human factor that is decisive in the development of any state. Thus, the question of assessing the quality of life of the population of Pakistan was covered by Lodhi et al (2019), of southeastern Poland by Ćwirlej-Sozańska et al (2018), of Germany by Huber et al (2017), of the capital of Slovenia, Ljubljana, by Tiran (2016), of the Dutch by Gobbens & van Assen (2018), of Romania and Lithuania by Streimikiene (2014), of Italy by Bonatti et al (2017), Cecchini et al (2019). The factors affecting the decline in quality of life include the environmental component (Streimikiene, 2014;Gobbens & van Assen, 2018), aging of the population (Ćwirlej-Sozańska et al, 2018;Lodhi et al, 2019), increasing number of chronic diseases (Ćwirlej-Sozańska, 2018), rural residence (Lodhi et al, 2019), quality of living conditions (Tiran, 2016;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is because, in many cases, boundaries of local administrative units were originally traced by considering environmental constraints and territorial elements (e.g., mountains, rivers, lakes, road and railway infrastructures, harbors, accessibility, amenities), shaping the socioeconomic profiles of local communities in turn. Municipalities were therefore adopted as a spatial proxy of local systems in empirical studies using official statistics and covering long time intervals (e.g., [6,22,31,36]). Earlier studies carried out in rural districts of Southern Europe sharing similar characteristics with the study area have evidenced how municipalities are homogeneous local units that are appropriate for a quali-quantitative analysis of socioeconomic resilience.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Ferrara et al [22] expanded this interpretative framework to more than 30 municipalities in the Basilicata region in Southern Italy, which were considered as appropriate spatial units for analysis of 'fast' and 'slow' drivers of change and socioeconomic resilience of local systems. A similar framework was applied at the national scale in Greek municipalities [31] and, more specifically, in a rural district of Crete, Southern Greece, where extensive studies of resilience to external shocks were carried out by considering local municipalities as spatial proxies that delineate socio-environmental dynamics better than other reference units [43]. A similar approach was also applied-although in a partial fashion-in Spain [72], and a pilot study was finally carried out for three countries of Southern Europe (Spain, Italy, and Greece) using the same spatial scale under the same assumptions [85].…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation